Analysis of Women's Participation in Improving the Family Economy (Case Study of Traders at Panciro Market, Gowa Regency) - Kasmia, Kasmia; Suarni, Agusdiwana; Asriati, Asriati (Perpustakaan dan Penerbitan Unismuh Makassar, 2022)
This study entitled “Analysis of Women's Participation in Improving the Family Economy (Case Study of Traders in Panciro Market, Gowa Regency)”. This study aims to determine women's participation in improving the family economy in Panciro Market, Gowa Regency. This type of research is a qualitative research method. The processed data is the result of interviews with Anwar Malolo, the Head of Panciro Village and 20 women who work as traders in Panciro Market, Gowa Regency. Data collection methods used in this research are observation, interview and document study where the author sees the situation directly in the field. The results showed that the participation of women in improving their family's economy was 47% of the total 20 informants based on income indicators. This means that on average the income from his business as a trader has helped to meet the needs of the family, which directly with their participation is able to improve the economic condition of his family